Argumentativeness, Avoidance, Verbal Aggressiveness, and Verbal Benevolence as Predictors of Partner Perceptions of an Individual's Conflict Style. (May 2014) - Guerrero, Laura K.; Gross, Michael A.
Abstract This study addressed two main questions. First, are the traits of argumentativeness, verbal aggressiveness, avoidance, and verbal benevolence reflected in conflict styles such that they are perceived by others? Second, how do these traits predict the five conflict styles in the dual concern model? These questions were tested using dyadic data from a simulated downsizing activity. Results showed that participants perceived their partners differently depending on the traits their partners endorsed. For example, people who reported being avoidant or verbally aggressive were less likely to be perceived as using the compromising style. Overall, the results suggested that the four traits investigated in this study are likely to be associated with observable behavior. Findings also demonstrated that these traits help differentiate the five conflict styles in more nuanced ways than predicted by the dual concern model. Finally, the results supported the idea that conflict styles are not only shaped by one's own traits but also by the traits of others and the interaction between two people's traits.